2010
DOI: 10.1159/000321711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cytological Effects of Pimecrolimus Cream 1% after Resolution of Active Atopic Dermatitis Lesions by Topical Corticosteroids: A Randomized Controlled Trial

Abstract: Background: Topical pimecrolimus may maintain remissions of atopic dermatitis (AD) by inhibiting subclinical inflammation. Objective: To evaluate clinical and cytological effects of pimecrolimus in topical corticosteroid-treated and resolved AD lesions. Methods: Patients (n = 67) with resolved AD lesions were randomized to 3-week double-blind treatment with either pimecrolimus cream 1% or vehicle cream. Outcome measures were reduction in Eczema Area and Severity Index (EASI) and number of leukocytes in skin bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 88 publications
0
6
0
2
Order By: Relevance
“…42 Although both topical steroids and TCIs (particularly pimecrolimus) reduced T-cell numbers, LCs were only affected by steroids. 43 Despite its lesser effects, pimecrolimus showed better effects on extracellular lipids and lamellar bodies compared with topical steroids. 44 A recent clinical trial with topical steroids (lacking vehicle control) showed that even a mild-to-moderate steroid, such as triamcinolone acetonide 0.025%, is able to improve clinical indices and also restore key epidermal and immune skin abnormalities in AD lesions.…”
Section: Discussionmentioning
confidence: 99%
“…42 Although both topical steroids and TCIs (particularly pimecrolimus) reduced T-cell numbers, LCs were only affected by steroids. 43 Despite its lesser effects, pimecrolimus showed better effects on extracellular lipids and lamellar bodies compared with topical steroids. 44 A recent clinical trial with topical steroids (lacking vehicle control) showed that even a mild-to-moderate steroid, such as triamcinolone acetonide 0.025%, is able to improve clinical indices and also restore key epidermal and immune skin abnormalities in AD lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The predisposition to xerosis may also include other skin barrier-related genes such as Spink5, kallikrein 7 or hornerin [19,20,21]. It has been shown that atopic dermatitis may be associated with subclinical inflammation which could contribute to pruritus in elderly patients with xerosis and a history of atopic dermatitis [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluated lesional skin biopsies and focused on T cell subsets. [35][36][37][38][39][40] Evaluation of alpine climate treatment has been focused on a reduction in eosinophil numbers, but data on T-and B cell subsets are limited. 14,15 Here, we investigate blood T-and B cell subsets in children with moderate to severe AD before and after an intensive 6-week treatment protocol.…”
Section: Despite These Insights Into T Cell and B Cell Abnormalities mentioning
confidence: 99%
“…Despite these insights into T cell and B cell abnormalities in disease, data about the effects of treatment on the immune response in patients with AD are limited. Most studies evaluated lesional skin biopsies and focused on T cell subsets . Evaluation of alpine climate treatment has been focused on a reduction in eosinophil numbers, but data on T‐ and B cell subsets are limited …”
Section: Introductionmentioning
confidence: 99%